Association Between Hearing Loss and Systemic Small-Vessel Vasculitis: Audiological Aspects Across Disease Types - Vija Vainutienė; Eugenijus Lesinskas; Tatjana Ivaškienė; Diana Mieliauskaitė; Jolanta Dadonienė; Dalia Miltinienė; Justinas Ivaška (Medicina, 2025)
Background and Objectives: Systemic small-vessel vasculitis (SV) represents a group of rare autoimmune disorders with varied etiologies and clinical manifestations. Audiovestibular involvement in SV may present with a broad spectrum of symptoms, often complicating diagnosis and management. This study aimed to evaluate auditory function and speech perception in individuals diagnosed with SV and to investigate associations with disease-specific clinical parameters. Materials and Methods: A total of 40 patients diagnosed with SV (mean age: 48.9 years; range: 28–65 years) were recruited for comprehensive audiological assessment. The evaluation protocol included otoscopic examination, tympanometry, pure-tone audiometry, and speech audiometry. Statistical analysis was conducted using R software (version 4.3.1), and significance was set at p < 0.05. Results: Diagnoses included granulomatosis with polyangiitis (52.5%), eosinophilic granulomatosis with polyangiitis (27.5%), necrotizing vasculopathy (12.5%), and microscopic polyangiitis (7.5%). Mean disease duration was 4.14 years. Hearing complaints were reported by 77.5%; in 20%, they were the initial symptoms. Audiometry identified hearing loss in 50% of patients—predominantly sensorineural (33.8%), followed by mixed (13.7%) and conductive (2.5%) types. Hearing loss was most frequent in necrotizing vasculopathy (60%) and among ANCA-positive individuals (53.7%). Conclusions: Sensorineural hearing loss is common in SV, particularly in ANCA-positive patients, highlighting the need for routine hearing assessment in SV management.